2016
DOI: 10.4025/actascihealthsci.v38i2.28775
|View full text |Cite
|
Sign up to set email alerts
|

<b>Coconut oil increases HDL-c and decreases triglycerides in wistar rats

Abstract: ABSTRACT. Changes in body composition and serum lipid profile in rats, supplemented with coconut oil, are evaluated and compared to other lipid sources. Female Wistar rats received by gavage 1 mL kg -1 of saline, soybean oil, lard or coconut oil during 21 days. At the end of the study period, body composition, food intake, feces, urine, organ weight and serum lipid profile were assessed. No statistical differences between the groups were found in body composition, food intake, fecal and urinary analysis, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Supplementation with the oils did not influence the animals' food intake since there was no statistical difference between the study groups, which the FEC also evidenced. Santana et al (2016) showed similar results regarding food intake, with no difference in food intake between the control group and the groups supplemented with different lipid sources. However, it showed a significant difference in FEC between the groups treated with lard and soybean oil.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Supplementation with the oils did not influence the animals' food intake since there was no statistical difference between the study groups, which the FEC also evidenced. Santana et al (2016) showed similar results regarding food intake, with no difference in food intake between the control group and the groups supplemented with different lipid sources. However, it showed a significant difference in FEC between the groups treated with lard and soybean oil.…”
Section: Resultsmentioning
confidence: 56%
“…Moreover, it has been suggested that medium chain saturated fatty acids oil does not raise total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C). They significantly increased HDL-C concentrations in experimental rats (Santana et al, 2016). Furthermore, there is evidence that consumption of monounsaturated oils (olive oil and nuts) led to improved lipid profiles and a decreased risk of cardiovascular disease (Khaw et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
“…Saturated fats that is rich in lauric acid provide a favorable lipid profile and so, virgin coconut oil helps in the prevention of cardiovascular atherosclerotic diseases. The consumption of virgin coconut oil exhibits anti-inflammatory, anti-oxidant, and antidiabetic properties (Santana et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…O óleo de coco é um suplemento alimentar de origem vegetal derivado da espécie Cocos nucifera, da família Arecaceae e da subfamília Cocoideae 1 . Sua composição é basicamente de ácidos graxos saturados (92%) e os principais são o ácido láurico, ácido mirístico e o ácido palmítico 2 .…”
Section: Introductionunclassified
“…Os estudos tem mostrado que diferentes programas de exercícios físicos podem alterar a composição corporal e melhorar o perfil lipídico 15,[16][17][18] . No entanto, quando se associa os exercícios físicos com estratégias dietéticas, como a suplementação com óleo de coco, encontramos investigações com modelos animais 1,[19][20][21] e somente um estudo realizado com seres humanos 10 . São necessários mais estudos que comprovem os supostos benefícios do óleo de coco na composição corporal e parâmetros lipídicos em humanos.…”
Section: Introductionunclassified